LA REVOLUCIÓN DIGITAL EN LA INSCRIPCIÓN Y PROYECCIÓN EN FESTIVALES - Ismael Martín (Fonseca, Journal of Communication, 2023)
The last few years have been profound changes in the formats of film and festivals. He is not a simple evolution of analogue formats, but a rupture, a revolution that has transformed the way in which look and feature films at festivals, and how the projections are managed.This revolution has given place to new professions, and the disappearance of others, has changed the way to distribute and exhibit movies. Few sectors have suffered such a radical change in such a short time; from the year 2012 that copies were being used in 35 mm, to the present day in which this format has virtually disappeared.